Service Models in the Public Sector - Kuno Schedler; Ali Asker Guenduez (Yearbook of Swiss Administrative Sciences)
This study investigates service models within the public sector and explores the government’s role in delivering services. While extensive research has been conducted on business models in the private sector, the exploration of business models in the public sphere has received comparatively limited attention. To address this gap, our study adopted a comprehensive multi-method approach that combined both inductive and deductive methods. Through inductive analyses of real-world cases, we gathered rich and detailed information that allowed us to uncover patterns, trends, and the unique characteristics of these service models. Simultaneously, we drew upon the existing body of literature on service delivery, harnessing theoretical descriptions and concepts that guided our analysis and interpretation of the findings. Our work has led to the identification and comprehensive description of 45 different public sector service models. In closely analyzing the models, we were able to uncover five distinct roles that the government plays when operating these service models. This study offers new implications for the development and adaptation of innovative service models in the public sector. Highlights • We identify and analyze 45 service models in the public sector. • We categorize five government roles in service models: Activator, Yield Shaper, Funder, Guardian of Public Goods, Performance Designer. • Our study offers insights into adapting and innovating service models in the public sector. Zusammenfassung Diese Studie untersucht Servicemodelle im öffentlichen Sektor und beleuchtet die Rolle des Staates bei der Bereitstellung von Dienstleistungen. Während umfangreiche Forschungen zu Geschäftsmodellen im privaten Sektor durchgeführt wurden, hat die Erforschung von Geschäftsmodellen im öffentlichen Bereich vergleichsweise wenig Beachtung gefunden. Um diese Lücke zu schliessen, haben wir in unserer Studie einen umfassenden Multi-Methoden-Ansatz verwendet, der sowohl induktive als auch deduktive Methoden kombiniert. Durch induktive Analysen realer Fälle haben wir detaillierte Informationen gesammelt, die es uns ermöglichten, Muster, Trends und die einzigartigen Merkmale dieser Servicemodelle aufzudecken. Gleichzeitig haben wir auf das bestehende Wissen zur Servicebereitstellung zurückgegriffen und theoretische Beschreibungen und Konzepte genutzt, die unsere Analyse und Interpretation der Ergebnisse leiten. Unsere Arbeit identifiziert und beschreibt 45 verschiedenen Servicemodellen im öffentlichen Sektor. Bei der genauen Analyse der Modelle haben wir fünf unterschiedliche Rollen des Staates bei der Anwendung dieser Servicemodelle aufgedeckt. Die Studie liefert neue Implikationen für die Entwicklung und Anpassung innovativer Servicemodelle im öffentlichen Sektor. Résumé Cette étude examine les modèles de service dans le secteur public et met en lumière le rôle du gouvernement dans la prestation de ces services. Alors que de nombreuses recherches ont été menées sur les modèles d’entreprise dans le secteur privé, l’exploration des modèles d’entreprise dans le domaine public a reçu relativement peu d’attention. Afin de combler cette lacune, nous avons utilisé une approche méthodologique complète combinant des méthodes inductives et déductives au sein de notre étude. Grâce à des analyses inductives de cas réels, nous avons collecté des informations détaillées qui nous ont permis de révéler les tendances, les schémas et les caractéristiques uniques de ces modèles de service. Parallèlement, nous nous sommes appuyés sur les connaissances existantes en matière de prestation de services et avons utilisé des descriptions et des concepts théoriques afin d’orienter notre analyse et notre interprétation des résultats. Notre travail identifie et décrit 45 modèles de service différents dans le secteur public. Une analyse approfondie de ces modèles nous a permis de mettre en évidence cinq rôles distincts du gouvernement dans l’application de ces modèles de service. Cette étude apporte de nouvelles implications pour le développement et l’adaptation de modèles de service innovants dans le secteur public. Schlüsselwörter: Servicemodell; Geschäftsmodell; Rolle; öffentliche Verwaltung; öffentlicher Sektor; Staat Mots Clés: modèle de service; modèle d’entreprise; rôle; administration publique; secteur public; gouvernement